PENINGKATAN KUALITAS PRODUK SHARP CONTAINER MENGGUNAKAN METODE QUALITY CONTROL CIRCLE DI PT. XYZ - Najibatul Mujahidah (2022)
Quality assurance is considered important because it can provide a sense of trust to consumers and ensure that all production activities are carried out by existing quality standards and adapted to consumer desires. The purpose of this research is to analyze the causes of dominant and non-dominant defects in PT. XYZ, the factors that are the main problems for improvement, as well as submit proposals related to improving product quality control with the Quality Control Circle (QCC) method, PDCA scheme, and analysis using seven tools and statistics processed using SPSS. The results of the study showed that the most defects in product production at PT. XYZ, namely torn defects with a total of 51, followed by dented defects with a total of 22, and color defects that do not match a total of 15. In addition, there is a further research plan including SOP which are used as a reference in conducting quality control and firm action against workers who do not comply with the SOP. properly and correctly, improving the existing standard operating procedures, as well as providing continuous training or training to employees